2013
DOI: 10.1371/journal.pntd.0002095
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of DENV-2 Activity in Brazil: Molecular Characterization and Phylogeny of Strains Isolated from 1990 to 2010

Abstract: In Brazil, dengue has been a major public health problem since its introduction in the 1980s. Phylogenetic studies constitute a valuable tool to monitor the introduction and spread of viruses as well as to predict the potential epidemiological consequences of such events. Aiming to perform the molecular characterization and phylogenetic analysis of DENV-2 during twenty years of viral activity in the country, viral strains isolated from patients presenting different disease manifestations (n = 34), representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 45 publications
1
37
0
2
Order By: Relevance
“…Before sequencing, the 1957 isolate had been passaged in suckling mouse brain, but the earlier passage history is unclear; the 2011 isolate was passaged twice in Vero cells. This 2.2% amino acid divergence is within the range that has been observed for other flaviviruses with isolations ranging between 1 and 49 years apart, [17][18][19] indicating relatively little change in the ENTV genome in 54 years since the first isolation.…”
supporting
confidence: 73%
“…Before sequencing, the 1957 isolate had been passaged in suckling mouse brain, but the earlier passage history is unclear; the 2011 isolate was passaged twice in Vero cells. This 2.2% amino acid divergence is within the range that has been observed for other flaviviruses with isolations ranging between 1 and 49 years apart, [17][18][19] indicating relatively little change in the ENTV genome in 54 years since the first isolation.…”
supporting
confidence: 73%
“…The percentage identity of the latter with strain DR59/01 (Dominican Republic) isolated in 2001, combined with the percentage of divergence with strains first introduced in the 1990s, suggests a new viral lineage introduced from the Caribbean. No consistent differences were observed on the E gene from strains isolated from cases with different clinical manifestations [33]. …”
Section: Resultsmentioning
confidence: 99%
“…Intra-serotype antigenic variation and the resulting differential generation of protective antibodies and immune responses is postulated as one of the reasons for the high epidemiological impact of certain DENV serotypes in the Americas [60]. The lack of consistent differences in the E gene of Brazilian DENV-2 isolates from cases with different clinical manifestations suggests that if disease severity has a genetic basis, it is not solely due to differences observed in the E gene [33]. …”
Section: Discussionmentioning
confidence: 99%
“…aegypti salivary glands 7 days earlier than in American genotype, suggesting a 2-to 65-fold increase in the vectorial capacity of mosquitoes [134]. It has been shown that Asiangenotype DENV strains causing DHF share a particular substitution in the envelope protein E-N390D, which seems to be involved in viral replication in macrophages and dendritic cells, and is thus considered to be a virulence marker [136,137]. Further studies should be conducted in order to elucidate the genetic determinants of SEA genotype fitness in mosquitoes.…”
Section: Dengue Virusmentioning
confidence: 99%